Intercultural Communication in Improving the Competence of International Students on Instagram - Julia Magdalena Wuysang; Ira Patriani; Henky Fernando; Yuniar Galuh Larasati; Julkarnaen; Leanne Morin (Fenomena, 2025)
Intercultural communication disseminated on Instagram extends beyond visual content, encompassing culturally rich symbols that convey deep meanings. Despite its significance, this phenomenon has received limited scholarly attention. This study addresses this gap by examining intercultural communication practices on Instagram, focusing on language, culinary traditions, and performing arts content. Adopting a qualitative descriptive approach, the research explores how cultural elements are shared and represented through social media. The findings identify three primary contexts: (1) the use of native languages to introduce linguistic and cultural diversity; (2) the dissemination of traditional culinary content to reinforce cultural identity; and (3) the learning and sharing of traditional dance via Instagram as a strategy for preserving cultural heritage. These insights highlight Instagram’s role as an active, dynamic, and educational space for intercultural communication. Komunikasi antarbudaya yang tersebar melalui media sosial Instagram tidak hanya terbatas pada visualisasi konten, tetapi juga merepresentasikan simbol-simbol budaya yang sarat makna. Fenomena ini masih kurang mendapat perhatian dalam kajian ilmiah. Studi ini bertujuan mengisi kekosongan tersebut dengan menganalisis praktik komunikasi antarbudaya dalam Instagram yang berfokus pada konten bahasa, kuliner, dan seni pertunjukan. Studi ini menggunakan pendekatan deskriptif kualitatif, dengan mengeksplorasi elemen-elemen budaya didiseminasikan melalui media sosial Instagram. Hasil penelitian mengidentifikasi tiga konteks utama: (1) penggunaan bahasa asli oleh penutur asli untuk memperkenalkan keragaman linguistik dan budaya; (2) penyebaran konten kuliner tradisional sebagai media penguatan identitas budaya; dan (3) pembelajaran tarian tradisional melalui Instagram sebagai strategi pelestarian warisan budaya. Temuan ini menegaskan bahwa Instagram berfungsi sebagai ruang aktif untuk komunikasi antarbudaya yang dinamis dan edukatif.